Corporate actions in human welfare: Resignifying recreation (EFRYD) - Gamboa Caicedo, Gloria Esperanza (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The present work aims to generate constructs whose intention is to reveal the embodied actions of human well-being in the light of a resignification of recreation in the Colombian context. Under the gaze of the interpretive paradigm supported by phenomenology and hermeneutics as a methodology, the information was collected through interviews with a group of Professors with long experience at the university who served as key versioners, later the constant comparative method was applied, giving rise to the mixed categorization and triangulation that favored the process of generation of theoretical constructs, emerging among the findings: the plurality of theoretical approaches in the process of Educational Labor Well-being: Recreation and Corporeal, Comprehensive, cultural, social quality of life, The Tree of